Urinary Stone Disease and Preventable Nephrectomies - Shrestha, Anil; Chhettri, Prakash; Yadav, Birendra Kumar; Basnet, Robin Bahadur; Shrestha, Parash Mani (Journal of Nepal Health Research Council, 2019)
Background: Urinary stone disease has high prevalence in our belt. The end stage complication of this disease turns out to be a non-functioning kidney, which in fact could be prevented by means of appropriate treatment and follow up. Methods: This is retrospective study of the nephrectomy cases of last 8 years retrieved from the hospital database. Variables like age, sex, indications for nephrectomy, modalities of nephrectomy and morbidities among the primary and recurrent disease were taken into consideration. Analysis were done using Microsoft Excel 2016. Results: Five hundred and twenty-nine nephrectomies were performed in last 8 years at our hospital. Female were more prone for nephrectomies. Age at third and fourth decade were most to be affected. Ninety percentage of nephrectomies were done for benign causes, 65% for the stone disease. The recurrent renal stone disease without any past surgical interventions were more prone to undergo nephrectomies. The conventional open technique of nephrectomy has largely been replaced by laparoscopic means in recent years. Conclusions: The main contributor for nephrectomy in our context is urinary stone disease, which is considered to be the preventable factor Keywords: Nephrectomy; renal stone; urinary stone disease.